Determinants of Malnutrition in Senegal : Individual, Household, Community Variables, and Their Interaction - Linnemayr, Sebastian; Alderman, Harold; Ka, Abdoulaye (2012)
The relationship between poverty and nutrition is a two-sided one: on the one hand, economic growth (which is generally associated with an eradication of poverty) leads to reduced malnutrition. On the other hand, nutrition is one of the key ingredients for human capital formation, which in turn represents one of the fundamental factors of growth. There are numerous studies that show the correlates of malnutrition using both household- and community-level variables. However, few of these studies allow for the potential endogeneity of community infrastructure or indicate their interplay with characteristics of the mother. The current study considers the socio-economic determinants of child malnutrition and investigates how programs compensate for the increased risks facing young mothers and their children or substitute for a low social status of the mother in the household. The empirical results show that children of mothers giving birth at a young age are disadvantaged in terms of their anthropometric status. Interaction effects of the presence of a non-governmental organization (NGO) or a health post in the village with characteristics of the mother stress the important role played by these institutions in helping disadvantaged mothers overcome their difficulties. These findings have implications for efficient program design and represent a further step towards gaining an improved understanding of the complex determinants of child (mal)nutrition.